RANCANG BANGUN SISTEM REKOMENDASI PENGADAAN INVENTARIS BUKU DI PERPUSTAKAAN SMK NEGERI 1 KEPANJEN - Yoyok Seby Dwanoko, S.Kom., M.Kom, Yonathan Ari Wibowo (Jurnal Fakultas Teknologi Informasi, 2014)
AbstrakPenerapan teknologi informasi telah menyebar hampir di semua bidang, tidak terkecuali di bidang perpustakaan. Perpustakaan adalah institusi/lembaga yang menyediakan koleksi bahan perpustakaan tertulis, tercetak, dan terekam sebagai pusat sumner informasi yang diatur menurut sistem dan aturan yang baku dan didayagunakan untuk keperluan pendidikan, penelitian, dan rekreasi intelektual bagi masyarakat. Perpustakaan secara umum bertujuan untuk melakukan layanan informasi literal pada masyarakat.Penggunaan aplikasi perpustakaan ini bertujuan untuk merekomendasi pengadaan buku baru yaitu proses pembelian buku yang dilihat dari transaksi peminjaman bulanan dan dari banyaknya kategori buku yang telah dipinjam oleh anggota perpustakaan, sehingga bisa didapatkan kategori buku apa yang paling diminati oleh peminjam.Kata kunci : Sistem Rekomendasi, Pengadaan Inventaris Buku, PerpustakaanÂ ABSTRACTThe assembling of Technology Information has spread almost in every field, include the library. Library is an institution which provides the library written substance, formed, and recorded as the center of the Information source that is arranged based on the system and the base rule and use in education needed, a research, and intellectual recreation for the people. Generally, the purpose of the library is doing the Literal Information service to the people. Based on this purpose, SMK Negeri 1 Kepanjen Library is a Library which provides some books which can improves the teaching learning process for teachers and students. But, there is a problem that is the system of Book inventory Stock is not arranged well. Thus, needed a recommendation system to help the Book Inventory Stock process. Â This system is made by using VB.Net, Program database SQL Server, and for the planning like Use Case, Activity, and Class Diagram uses Astah Community.Â After doing the testing by usingâ Blackbox Testingâ, the result from this implementation is a system which can doing the total borrowed amount based on the book category which is borrowed in each period. Thus, it will helps in Inventory Book Stock recommendation.Keywords : Recommendation System, book inventory stock, libraryÂ